Pengaruh Lingkungan Kerja Fisik Dan Job Insecurity Terhadap Produktivitas Kerja Karyawan PT. Japfa Comfeed Indonesia Tbk Lampung - Widia, Anggawidia; Thaib, Muprihan; Bandarsyah; Zulanda Putri, Reisa Dyasvaro (Jurnal Bisnis Darmajaya, 2025)
The decline in employee productivity has become a crucial issue in the agribusiness industry, demanding attention to internal factors such as the physical work environment and job insecurity. This study aims to evaluate the influence of the physical work environment and job insecurity on employee productivity in the agribusiness manufacturing sector. A quantitative research approach was employed using purposive sampling, involving 45 respondents from the production department. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 20. The results indicate that both independent variables have a significant influence both partially and simultaneously on employee productivity. These findings emphasize the importance of fostering a supportive work environment and ensuring job stability to enhance employee performance in a sustainable manner.